Iron tablets and vitamin C (1000 mg): Can they enhance haemoglobin levels and cardiovascular capacity in female martial athletes? - Made, Budiawan; Luhur, I Made Jati; Widiarta, Made Bayu Oka (Journal Sport Area, 2023)
Regarding nutrition, providing proper food intake can produce optimal physical conditions and provide sufficient energy. This research aimed to prove that combining iron tablets and 1000 mg of vitamin C can increase hemoglobin levels and maximum oxygen volume in female athletes in martial arts. This research used an experimental group design by using a randomized post-test-only control group design. It used 40 female athletes divided into four groups and carried out for 12 weeks. The control group was given a placebo, treatment group one was given iron tablets three times a week, treatment group two was given 1000 mg of vitamin C three times a week, and treatment group three was given a combination of iron tablets and 1000 mg vitamin C. The results show that the mean of hemoglobin levels in the group given iron tablets is 13.23 ± 1.09 g/dL, vitamin C is 12.69 ± 0.89 g/dL, and a combination of iron tablets and vitamin C is 14.50 ± 1.40 g/dL significantly higher (p < 0.05) than the control group, namely 11.93 ± 1.08 g/dL. The average maximum oxygen volume level in the group given iron tablets is 41.24 ± 0.52 ml/Kg/minute, vitamin C is 40.58 ± 0.66 ml/Kg/min, and a combination of iron tablets and vitamin C is 43.33 ± 0.41 ml/Kg/min which is significantly higher (p < 0.05) compare to the control group’s average of 38.33 ± 0.42 ml/Kg/min. It concludes that giving iron and vitamin C tablets to female martial arts athletes can significantly increase hemoglobin levels and maximum oxygen volume. Therefore, iron and vitamin C tablets are proven to contribute to overcoming the problem of anemia in women and are able to increase the cardiovascular capacity of athletes.